Invasive mucinous adenocarcinoma of the lung: Serial CT findings, clinical features, and treatment and survival outcomes. Issue 12 (5th October 2020) - Beck, Kyongmin Sarah; Sung, Yeoun Eun; Lee, Kyo Young; Han, Dae Hee
Abstract : Background: Invasive mucinous adenocarcinoma (IMA) of the lung is a rare and distinct subtype of adenocarcinoma that can appear as airspace opacities on computed tomography (CT). In daily practice, we have occasionally encountered spontaneous regression of airspace opacities (SRAs) without treatment on serial CTs in patients with IMAs, which has not previously been described in the literature. Here, we describe serial CT findings with emphasis on SRAs in relation to clinicopathological features and treatment outcomes in patients with IMAs. Methods: A total of 46 patients with pathologically‐confirmed IMAs of the lung from January 2013 to June 2018 were included. Serial CT scans were reviewed and the patients were classified into SRA and no‐SRA groups according to the presence of SRA. Radiological features, clinicopathological characteristics, and treatment outcomes were compared between the SRA and no‐SRA groups. Results: A total of 32 patients were included in the no‐SRA group and 14 patients in the SRA group. IMAs in the SRA group were mostly pneumonic ( P < 0.001), larger ( P < 0.001), multifocal ( P = 0.001), and showed higher stage ( P < 0.001) on initial CT. Of seven patients who died during follow‐up, six were from the SRA group ( P < 0.001). Mean overall survival for all IMAs was 86.6 months (range, 0–110 months), and the SRA group showed significantly worse overall survival ( P < 0.001). Conclusions: IMAs of the lung showing SRAs on serial CTs are larger and multifocal, and tend to be pneumonic in type on initial CT. Patients present at a higher stage of disease, with higher mortality rate and reduced overall survival. Key points: Significant findings of the study: Invasive mucinous adenocarcinomas (IMAs) of the lung can show spontaneous regression of airspace opacities (SRAs) on serial CTs, without being correlated to the administration of anticancer drugs. IMAs that showed SRAs demonstrated reduced overall survival in patients. What this study adds: When airspace opacities show regression on CT, IMA should still be included in the differential diagnosis. A more careful application of RECIST 1.1 is needed in the assessment of tumor response of IMAs. Abstract : Invasive mucinous adenocarcinomas (IMAs) of the lung can show spontaneous regression of airspace opacities (SRAs) on serial CTs, not correlated with the administration of anticancer drugs. IMAs that show SRAs demonstrated reduced overall survival in patients. When airspace opacity shows regression on CT, IMA should still be included in the differential diagnosis and a more careful application of RECIST 1.1 is needed in the assessment of tumor response of IMAs.